Who is to blame for the ‘problem’ of teenage pregnancy? Narratives of blame in two South African communities - Zoe Duby; Brittany Bunce; Chantal Fowler; Kate Bergh; Kim Jonas; Nevilene Slingers; Catherine Mathews; Fareed Abdullah (Reproductive Health)
Abstract Background The framing of teenage pregnancy in social discourse influences the way in which adolescent girls and young women (AGYW) are treated, the extent to which they are supported, and to which they are able to engage with services and enact pregnancy prevention behaviours. Methods Through the analysis of data from a qualitative study conducted in the South African communities of Newcastle in KwaZulu-Natal and Moretele in the North-West province, we explored narratives of blame for teenage pregnancy. Data derived from seventy-one in-depth interviews conducted with forty AGYW aged between 15 and 24, twenty-four parents/caregivers of AGYW, five service providers, ten school educators, and two other community members. Interpretation of data drew upon blame, attribution and framing theories. Findings The overall framing of teenage pregnancy was overwhelmingly negative, with participants labelling it immoral and ‘wrong’. Findings were arranged into key thematic areas that emerged in the data relating to blame for teenage pregnancy: the individual centred ‘wrong-girl’ and developmental discourses, in which blame was apportioned to AGYW for being immature, reckless, irresponsible, disobedient and greedy; the ‘wrong-family’ discourse in which blame was attributed to parents of AGYW for poor parenting and failing to adequately care for the adolescents in their responsibility; the ‘wrong-men’ discourse in which blame was attributed to men for luring AGYW into transactional sex, and for perpetrating gender-based violence; and lastly the ‘wrong-society’ discourse which attributed blame to contextual/structural factors such as poverty, a high volume of unregulated drinking establishments, and a lack of youth-friendly services. Conclusions Policies, interventions and programmes focusing on adolescents’ sexual and reproductive health need to carefully consider the framing and narratives of blame and responsibility. There is an urgent need to shift away from the individualised moralistic shaming of pregnant AGYW, towards a recognition of a complex interplay of multilevel factors that enable or constrain AGYW’s agency. Policies and programmes should focus on both providing sufficient support to AGYW, while also addressing structural factors and harmful narratives and thus create the conditions necessary to enable AGYW to enact safe, informed, agentic and responsible decisions and behaviours about their own sexual and reproductive health.